2006
DOI: 10.1111/j.1365-2249.2006.03136.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-A (UVA-1) radiation suppresses immunoglobulin production of activated B lymphocytesin vitro

Abstract: SummaryPrevious studies have shown that low-dose ultraviolet-A (UVA-1) total body irradiations were capable of improving disease activity in patients with systemic lupus erythematosus (SLE). We hypothesized that UVA-1-induced suppression of immunoglobulin production by activated B cells in the dermal capillaries could be (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 21 publications
4
27
0
1
Order By: Relevance
“…Increased apoptosis of skin‐infiltrating white blood cells has also been reported following UVA‐1 radiation . Furthermore, attenuated B‐cell immunoglobulin production and lower anti‐dsDNA titers were found with UVA‐1 exposure in vitro .…”
Section: Uva‐1 Therapy For Lupus Patientsmentioning
confidence: 88%
See 1 more Smart Citation
“…Increased apoptosis of skin‐infiltrating white blood cells has also been reported following UVA‐1 radiation . Furthermore, attenuated B‐cell immunoglobulin production and lower anti‐dsDNA titers were found with UVA‐1 exposure in vitro .…”
Section: Uva‐1 Therapy For Lupus Patientsmentioning
confidence: 88%
“…Increased apoptosis of skin-infiltrating white blood cells has also been reported following UVA-1 radiation (51). Furthermore, attenuated B-cell immunoglobulin production and lower anti-dsDNA titers were found with UVA-1 exposure in vitro (52). Despite these promising results, UVA-1 radiation in SLE patients is not a common therapeutic modality.…”
Section: Uva-1 Therapy For Lupus Patientsmentioning
confidence: 99%
“…jor histocompatibility complex (MHC) with a vital role in the immune system (15). Another study has shown that UV radiation causes apoptosis of B lymphocytes, resulting decrease in immunoglobulins such as IgM, IgG, IgA, and IgE (16).…”
Section: Introductionmentioning
confidence: 99%
“…UVA radiation without riboflavin induced lymphocyte apobiosis (20–21). Our preliminary data also showed that more than 70% of lymphocytes was inhibited following treatment with UVA radiation.…”
Section: Introductionmentioning
confidence: 99%